Metodologi Pendekatan Sistemik: Metode Manajerial Mendasar Dan Powerful Yang Perlu Diimplementasikan - Indrawati, Chatarina Dian; Pitoyo, Didik Joko; Murdapa, Petrus Setya (JUSTER : Jurnal Sains dan Terapan, 2024)
Large-scale problems are complex and interrelated. Decisions made in these matters can have unexpected impacts. A systemic approach is a management method that can be used to solve systemic problems. This approach consists of two models, namely a qualitative model and a quantitative model. Qualitative models ensure that the issue is fully understood, while quantitative models allow for analysis of policy scenarios. In this article, the systemic approach methodology is briefly discussed. This methodology begins with a qualitative formulation in the form of a causal-loop diagram. Causal-loop diagram is a diagram that describes the cause-and-effect relationship between variables in a system. Next, this methodology is continued with quantitative formulation in the form of stock-and-flow diagrams. Stock-and-flow diagram is a diagram that depicts the flow and supply of resources in a system. Further computations for experimental purposes (up to policy scenario simulations) can be implemented using Vensim® software. This article discusses the systemic approach methodology up to the experimentation example stage.